The Relationship between Self-Efficacy and Decision to Pursue Higher Education - Azmi, Ad Dein Imran; Rodzalan, Shazaitul Azreen (Research in Management of Technology and Business, 2026)
Education plays a pivotal role in national development, yet Johor, a key economic and demographic hub in Malaysia, faces a critical challenge in retaining SPM graduates within the higher education pipeline, as a significant number of students choose not to pursue further studies, leading to potential gaps in human capital development and limiting the socioeconomic prospects of these youth. This study explores the relationship between self-efficacy and the decision to pursue higher education among Form Five students in Muar, Johor, Malaysia. Recent trends indicate a growing number of Sijil Pelajaran Malaysia graduates are choosing not to continue their studies. With specific objectives to identify the level of self-efficacy among the students, determine their level of decision to pursue higher education, and examine the relationship between self-efficacy and their decision to continue theirstudies Utilizing a quantitative research design, this study distributed a structured questionnaire to Form Five students across Muar Johor. The instrument measured levels of self-efficacy, key influencing factors, and students’ decision regarding higher education. Data was analyzed using descriptive statistics, and correlation. The findings for Objective 1 indicate that Form Five students in Muar, Johor generally demonstrated a moderate to high level of self-efficacy, while the results for Objective 2 show that students also exhibited a relatively positive inclination toward pursuing higher education. The findings further indicate a positive relationship between self-efficacy and the decision to pursue higher education among Form Five students in Muar, Johor, with higher self-efficacy associated with a clearer intention to continue their studies.